2013
DOI: 10.1371/journal.pone.0054627
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers in Sex Hormone Pathway Genes Associated with the Efficacy of Androgen-Deprivation Therapy for Prostate Cancer

Abstract: Although most advanced prostate cancer patients respond to androgen-deprivation therapy (ADT), the efficacy is widely variable. We investigated whether the host genetic variations in sex hormone pathway genes are associated with the efficacy of ADT. A cohort of 645 patients with advanced prostate cancer treated with ADT was genotyped for 18 polymorphisms across 12 key genes involved in androgen and estrogen metabolism. We found that after adjusting for known risk factors in multivariate Cox regression models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…This brings us to the third question being addressed in this review- can diagnostic tools identify aggressive PCa from non-aggressive PCa. It is recognized that aging cannot be reversed, but, genetic tests such as association of various clinical characteristics with single nucleotide polymorphisms (SNPs) can be used for early diagnosis and personalized treatment [12,98,99]. The use of prostate-specific antigen (PSA) levels in PCa diagnosis is still controversial [100].…”
Section: Discussionmentioning
confidence: 99%
“…This brings us to the third question being addressed in this review- can diagnostic tools identify aggressive PCa from non-aggressive PCa. It is recognized that aging cannot be reversed, but, genetic tests such as association of various clinical characteristics with single nucleotide polymorphisms (SNPs) can be used for early diagnosis and personalized treatment [12,98,99]. The use of prostate-specific antigen (PSA) levels in PCa diagnosis is still controversial [100].…”
Section: Discussionmentioning
confidence: 99%
“…Second, all the patients with PC in our study possessed an average age of 74 years and exhibited high mortality during follow-up (48.2% in the ADT group and 35.6% in the non-ADT group). Yu et al 33 reported that two genetic markers, namely, AKR1C3 rs12529 and AR-CAG repeat length, are significantly associated with PC-specific mortality. In addition, the genetic polymorphism of AKR1C3 rs12529 could also minimise ADT-related impact on quality of life in patients with PC 34.…”
Section: Discussionmentioning
confidence: 99%
“…The association of clinicopathologic characteristics with time to BCR and PCSM was assessed using a log-rank test or Cox regression analysis. Multivariate Cox proportional hazard regression analysis was used to assess the effect of each SNP on clinical outcomes while adjusting for clinicopathologic variables, as previously described 27 29 30 31 32 33 34 35 . In the patient cohort with localized prostate cancer, explanatory variables included the known prognostic factors of age, PSA value at diagnosis, pathologic Gleason score, and tumor stage.…”
Section: Methodsmentioning
confidence: 99%